Quantifying the Sensitivity of Progressive Landslide Movements to Failure Geometry, Undercutting Processes and Hydrological Changes. Issue 2 (22nd February 2019) - Leshchinsky, Ben; Olsen, Michael J.; Mohney, Curran; O'Banion, Matt; Bunn, Michael; Allan, Jonathan; McClung, Reilly
Abstract: Many landslides cause destruction through progressive, gradual movements that stem from precipitation and toe erosion caused by marine or riverine processes. The magnitude and timing of seasonal landslide movement may be influenced by changing slide mass geometry and pore pressure response. The rate of landslide advance and potential for sustained movement has previously been studied in the context of hydrological factors, such as dilative or contractive pore pressure response, but the sensitivity of realistic landslide geometry subject to toe erosion is not well quantified. The purpose of this study is to assess the sensitivity of landslide movements to seasonal pore pressure increases and erosive processes. This assessment is performed through the development of a limit equilibrium framework couples time‐dependent feedback between coulomb friction, pore pressure, and evolving landslide geometry. This enables quantification of the relative influence of time‐dependent changes in pore pressure and rates of toe undercutting on landslide advance. The proposed model shows good agreement with monitoring data from three landslides in coastal Oregon, USA. Sensitivity to erosion, pore pressure, and geometry are assessed. Although fluctuations in pore pressures are found to be the primary driver for landslide movements at the sites, there is significant, nonlinear sensitivity to plausible erosion rates. This sensitivity is particularly apparent for landslides that tend to be short in length as the removal of buttressing materials is proportionally more destabilizing. These findings are an important consideration, particularly as increasingly extreme storm events that will likely magnify landslide movements in coastal or fluvial environments. Key Points: A model is presented that captures the coupled relationship between undercutting, pore pressure change, and progressive landslide movement The evolution of landslide geometry, undercutting rates, and pore pressure fluctuations influence the time‐dependent movements that are observed Smaller, progressive landslides demonstrate particular sensitivity to undercutting, highlighting the potential impacts of increased wave attack or fluvial erosion